AI IN THE MILITARY CYBER DOMAIN - ТРОФИМЕНКО, О. Г.; СОКОЛОВ, А. В.; ЧИКУНОВ, П. О.; АХМАМЕТЬЄВА, Г. В.; МАНАКОВ, С. Ю. (Technologies and Engineering, 2024)
Purpose. Analysis of the role of artificial intelligence (AI) in ensuring the cyber security of military networks and the possibility of applying AI in cybersecurity in defense. Methodology. The research used methods of analysis of scientific and literary sources, information search, comparison, and generalization. Findings. A comparison and analysis of publicly available information on AI-based cybersecurity technologies and tools was performed. As a result of the performed scientific analysis, it was established that AI tools play an important role in detecting and deterring threats of unauthorized intrusions into the security system of the military network. It has been found that AI is now a necessity for every computer system and network. The use of AI technologies in the form of intelligent agents is an effective tool for protecting against cyber attacks and assessing vulnerabilities and risks in cyberspace. During the 24/7 streaming analysis of large volumes of data in real-time, AI can identify patterns and provide recommendations for possible remediation of identified vulnerabilities. AI-powered cyber defense software responds to attacks by isolating affected systems. Originality. Areas of possible application of AI in military cyber operations were analyzed and systematized. Technologies of machine and deep learning, and artificial neural networks for identification and prediction of cyber threats are considered. Practical value. The obtained results of the performed analysis indicate the powerful potential of using intelligent technologies and tools for the military industry. AI technologies provide cybersecurity teams with flexibility, scalability, and the ability to automate threat detection. The implementation of AI in the cyber security of the military sphere can significantly reduce cyber risks, reduce costs, and optimize the processes of detection, research, response, and monitoring of cyber threats in real time. The paper contributes to the intensification of proactive detection and analysis of potential cyber threats in conjunction with incident and threat response activities in the fight against cybercrime. Ultimately, these advances will help our cyber military to be better prepared and equipped for the challenges and risks of modern warfare.